An assessment of a model-, grid-, and basin-independent tropical cyclone detection scheme in selected CMIP3 global climate models - Tory, Kevin; Chand, Savin; Dare, Richard; McBride, John (Journal of Climate, 2013)
A novel tropical cyclone (TC) detection technique designed for coarse-resolution models is tested and evaluated. The detector, based on the Okubo-Weiss-Zeta parameter (OWZP), is applied to a selection of Coupled Model Intercomparison Project, phase 3 (CMIP3), models [Commonwealth Scientific and Industrial Research Organisation Mark, version 3.5 (CSIRO-Mk3.5); Max Planck Institute ECHAM5 (MPI-ECHAM5); and Geophysical Fluid Dynamics Laboratory Climate Model, versions 2.0 (GFDL CM2.0) and 2.1 (GFDL CM2.1)], and the combined performance of the model and detector is assessed by comparison with observed TC climatology for the period 1970-2000. Preliminary TC frequency projections are made using the three better-performing models by comparing the detected TC climatologies between the late twentieth and late twenty-first centuries. Very reasonable TC formation climatologies were detected in CSIRO-Mk3.5, MPI-ECHAM5, and GFDL CM2.1 for most basins, with the exception of the North Atlantic, where a large un-derdetection was present in all models. The GFDL CM2.0 model was excluded from the projection study because of a systematic underdetection in all basins. The above detection problems have been reported in other published studies, which suggests model rather than detector limitations are mostly responsible. This study demonstrates that coarse-resolution climate models do in general produce TC-like circulations with realistic geographical and seasonal distributions detectable by the OWZP TC detector. The preliminary projection results are consistent with the published literature, based on higher-resolution studies, of a global reductionofTCs between about6%and 20%, withamuch larger spread of results (about 120% to 250%) in individual basins. © 2013 American Meteorological Society.